Exhaust Emissions from a Direct Injection Spark-Ignition Engine Fueled with High-Ethanol Gasoline - Miłosław Kozak; Marek Waligórski; Grzegorz Wcisło; Sławomir Wierzbicki; Kamil Duda (Energies, 2025)
Ethyl alcohol is a known additive to automotive gasoline. In commercially available gasolines, its concentration is between 5 and 10%. Since ethyl alcohol can be considered as a renewable fuel, efforts are being made to further increase its content in gasoline. This article describes the results of comparison experiments on a Euro 5 direct injection spark-ignition car engine fueled with conventional gasoline and gasoline with 30% v/v ethyl alcohol content (E30). The test results showed that a significant share of ethanol in the fuel did not affect most of the regulated emissions of gaseous components (namely: CO, HC, NO), i.e., a three-way catalyst effectively removed these components, regardless of the fuel composition. Slightly lower CO2 emissions with the E30 fuel were noticeable. A significant difference, however, in lower particulate number emissions for the fuel with high-ethanol content was seen. At high engine load, the use of the E30 fuel resulted in a tenfold reduction in particulate number emissions. This might be considered as a very valuable effect of ethanol since direct injection spark-ignition engines are typically characterized by higher particulate emissions compared to engines equipped with other types of injection systems.